Statistical model for impact and energy absorption of 3D printed coconut Wood-PLA - Kananathan, J.; Mahendran, Samykano; K., Kadirgama; Ramasamy, D.; Rahman, M. M (Tech Science Press, 2021)
Fused deposition modeling (FDM)-3D printing has been the favored technology to build functional components in various industries. The present study investigates infill percentage and infill pattern effects on the printed parts’ impact properties through the 3D printing technique using coconut wood-filled PLA composites. Mathematical models are also proposed in the present study with the aim for future property prediction. According to the ASTM standard, fifteen specimens with different parameter combinations were printed using a low-cost FDM 3D printer to evaluate their impact properties. Statistical analysis was performed using MINITAB to validate the experimental data and model development. The experimental outcomes reveal the honeycomb pattern with 75% infill density achieves the highest energy absorption (0.837 J) and impact energy (5.1894 kJ/m2). The p-value from statistical analysis clearly shows that all the impact properties are less than the alpha value of 0.05, suggesting all the properties are vital to determine the impact properties. The validation process affirms that the generated mathematical model for the energy absorbed and the impact energy is reliable at an acceptable level to predict their respective properties. The errors between the experimental value and the predicted value are 3.98% for the energy absorbed and 4.06% for impact energy. The findings are expected to provide insights on the impact behavior of the coconut wood-filled PLA composites prepared by FDM-3D printing and a mathematical model to predict the impact properties.